2017
DOI: 10.1515/jnet-2016-0088
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-osmosis in Membrane Systems: A Review

Abstract: We give a first review of experimental results for a phenomenon little explored in the literature, namely thermal osmosis or thermo-osmosis. Such systems are now getting increased attention because of their ability to use waste heat for separation purposes. We show that this volume transport of a solution or a pure liquid caused by a temperature difference across a membrane can be understood as a property of the membrane system, i. e. the membrane with its adjacent solutions. We present experimental values fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 61 publications
1
52
0
Order By: Relevance
“…A temperature difference can lead to a thermo-osmotic pressure. The magnitude as well as the direction of the thermo-osmotic water transfer depends on the membrane [ 86 ]. This additional term is little investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A temperature difference can lead to a thermo-osmotic pressure. The magnitude as well as the direction of the thermo-osmotic water transfer depends on the membrane [ 86 ]. This additional term is little investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and theoretical works have shown that the thermo-osmotic coefficient can be described as a function of the interfacial excess enthalpy distribution of the fluid and its hydrodynamic properties at the interface. 24 However, the influence of various factors on the mechanism of thermo-osmosis is still unclear. For example, the excess enthalpy distribution is affected by temperature, pressure, liquid polarity, 25 and liquid structure in the boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…This invention uses the fact that condensation of fluid on the receiving side gives rise to a hydrostatic pressure on this side, caused by a phenomenon called thermal osmosis. 14 The principle is illustrated in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…8,[23][24][25] Moreover, the interaction of the fluid with the membrane is widely ignored, even though it has been shown that the properties of the membrane can influence the flow direction. 14,26 For precise control of the flow, it is clearly important to distinguish between independent and dependent driving forces. For a quantitative description it is furthermore essential to account for the coupling between heat and mass transfer, as mass can also be transported by a temperature gradient, the so-called Soret effect.…”
Section: Introductionmentioning
confidence: 99%